ANALYSIS OF NOTARY HONORARY COUNCIL CONSENT AS GROUNDS OF IMPUNITY (STRAFUITSLAUTINGSGRONDEN) AGAINST REVELATION OF SECRETS - Gaza Carumna Iskadrenda; Anggita Mustika Dewi (Yustisia, 2017)
Article 66 paragraph (1) Act Number 2 of 2014 essentially regulates the consent of the Notary Honorary Council in the criminal justice process. The provisions in the a quo article have been still being applied and become a positive law in Indonesia. One of the criminal justice process in the notarial field relates to the criminal act of revelation of secrets as regulated in Article number 322 paragraph (1) of the Criminal Code. The consent given by the Notary Honorary Council as outlined above can certainly be viewed in the context of criminal law.The research is a normative legal research using secondary data of both primary legal materials and secondary legal materials. The data collecting technique used is documentary study with written materials as the data collection tool to be analyzed qualitatively using content analysis.The research result showed that in the context of criminal law, basically a notary who provides a copy of the deed and/or documents attached to the minuta deed or notarial protocol in the notarial archives for the purpose of the investigator, the public prosecutor or the judge has committed a criminal act of revelation of secrets as stipulated in Article number 322 paragraph (1) of the Criminal Code. However, the notary is not necessarily criminally liable considering the consent of the Notary Honorary Council as the grounds of impunity.Keywords: Notary Honorary Council consent, grounds of impunity, criminal act of revelation of secrets.